PENGARUH MOTIVASI KERJA DAN PELATIHAN SERTA PENGHARGAAN TERHADAP KINERJA INDEPENDEN HERBALIFE MEMBER (STUDI KASUS PADA PT HERBALIFE INDONESIA DI SAMARINDA PADA GROUP RAISA NEVADA DARANINGGAR) - DEISY NURHAFSARI; Dr. H. Ardi Paminto, SE, MS; Dr. Irwan Gani, SE, M.Si (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
ABSTRACT THE EFFECT OF WORK MOTIVATION AND TRAINING AND REWARD ON INDEPENDENT HERBALIFE MEMBER PERFORMANCE(CASE STUDY PT. HERBALIFE INDONESIA IN SAMARINDA ON GROUP RAISA NEVADA DARANINGGAR) DEISY NURHAFSARINIM. 1501026125             This research is motivated by the phenomenon that occurred at               PT Herbalife Indonesia in Samarinda in the Raisa Nevada Daraninggar group, It is known that during the last four years the performance of Independent Members has been considered low and has not been maximized in achieving the performance standards set by the company. Work motivation, training and reward are the most dominant factors to improve the performance of Independent Members.            The purpose of this study was to determine the effect of work motivation, training and reward for the performance of Independent Members. The population in this research are all Supervisors, World Teams, GET Teams in the Raisa Nevada Daraninggar group that are registered until December 31, 2017. The sample used was 47 people using the Simple Random Sampling technique. This study uses a quantitative approach, data for this study were obtained through a questionnaire. The data analysis method used is PLS (Partial Least Square).            The results of the study it was found that work motivation had a positive and significant effect on the performance of Independent Members. Training has a negative and not significant effect on the performance of Independent Members. Rewards have a positive and not significant effect on the performance of Independent Members.